2012
DOI: 10.1037/a0029941
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive predictors of reading and math achievement among gifted referrals.

Abstract: This study investigated the predictive power of the Wechsler Intelligence Scale for Children-Fourth Edition (WISC-IV) Full Scale IQ (FSIQ), the General Ability Index (GAI), and the WISC-IV index score composites on subsequent reading and math standardized test scores among high-achieving students. The sample consisted of 84 elementary-age students who received an individual cognitive assessment with the WISC-IV in the previous year as part of the application process for gifted and talented programming through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
3
13
0
2
Order By: Relevance
“…To conclude, our findings add to a growing body of research on the role of PASS cognitive processes in academic performance (e.g., Das et al, 2008; Georgiou et al, 2015; Joseph et al, 2003; Kroesbergen et al, 2010; Papadopoulos, 2001) suggesting that they can predict superior performance at least as good or better than other intelligence tests (e.g., Rowe et al, 2012; see also Hodges et al, 2018). However, using PASS scores to predict superior reading or mathematics performance has an added benefit; that PASS processes are rooted to a theory of intelligence (Luria, 1966) with close links to instruction (see Das & Misra, 2015).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…To conclude, our findings add to a growing body of research on the role of PASS cognitive processes in academic performance (e.g., Das et al, 2008; Georgiou et al, 2015; Joseph et al, 2003; Kroesbergen et al, 2010; Papadopoulos, 2001) suggesting that they can predict superior performance at least as good or better than other intelligence tests (e.g., Rowe et al, 2012; see also Hodges et al, 2018). However, using PASS scores to predict superior reading or mathematics performance has an added benefit; that PASS processes are rooted to a theory of intelligence (Luria, 1966) with close links to instruction (see Das & Misra, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…The objective of this study was to examine whether PASS processes could be used to predict superior academic performance. This is important in light of the dispute around the role of IQ in high achievement (e.g., Naglieri, 2008; Rowe et al, 2012) and the ever‐increasing attention of research to the role of neurocognitive processes (e.g., Naglieri & Otero, 2018). Our results showed that the four PASS processes were significantly related to both reading and mathematics and could accurately classify the children in the superior or non‐superior categories.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors influence students' performance in school and on standardized academic tests (Best & Miller, 2010;Dollinger & Clark, 2012;Duckworth, Quinn, & Tsukayama, 2012;Rowe, Miller, Ebenstein, & Thompson, 2012). One large influence on academic achievement is student on-task behavior and attention (Frazier, Youngstrom, Glutting, & Watkins, 2007;Rudasill, Gallagher, & White, 2010).…”
mentioning
confidence: 99%
“…The standard preference for instruments used as screening measures in the assessment of ASD is for them to be highly sensitive, such that all suspected cases of ASD receive appropriate evaluation (Norris & Lecavelier, ). Although no comparative discussions of various ASD assessment methods have taken place within school psychology, recent publications within the field have emphasized the importance of ongoing analysis of assessment tools and interpretation practices for children being evaluated for other concerns, such as attention deficit hyperactivity disorder (ADHD), intellectual disability, and learning problems (e.g., Ardoin et al., ; Bergeron & Floyd, ; Gutierrez & Vanderwood, ; Mercer, Harpole, Mitchell, McLemore, & Hardy, ; Rowe, Miller, Ebenstein, & Thompson, ; Stuebing, Fletcher, Branum‐Martin, & Francis, ). Thus, discussion of ASD assessment practices within school psychology appears to be in need of expansion, including a focus on which instruments are most appropriate for screening versus diagnosis/identification.…”
Section: Resultsmentioning
confidence: 99%